Wokół ewolucji języka - hipotezy o źródłach mowy ludzkiej i ich wartość naukowa - Boroch, Robert (Załącznik Kulturoznawczy, 2018)
The article refers to the hypotheses concerning the evolution of language presented in an article by Magdalena Danielewiczowa and entitled What is language needed for? What is necessary in language? The hypotheses proposed by Danielewiczowa have far reaching methodological consequences for cultural studies, especially those that strike a balance between general linguistics, linguistic semantics, anthropological linguistics, and philosophy of language. The organisation of research on cultural phenomena requires methodological planning enabling the minimum conditions of modern research methods to be met. These conditions are: (1) the definition of cognitive goals; (2) the determination of methods for the identification of variables (methodology); (3) research hypotheses formulated in affirmative (not interrogative or negative) sentences; (4) the existence of a relationship between the logical or analytical implications of variables and hypotheses; (5) the negation of hypotheses (counter-argumentation); (6) the substantiation of hypotheses. In this article I develop Danielewiczowa’s remarks on ways of using the term evolution, while also indicating the consequences of disregarding the conditions of correct reasoning within the framework of the research programme called anthropology of the word.